Metodología para elaborar balances y prospectivas energéticas en áreas geográficas de ecuador. Caso práctico: cadena energética eléctrica del área de concesión de la empresa eléctrica regional del sur. - Rojas Moncayo, Marco Vinicio (2017)
The present research thesis presents methodological proposals for the development of Energy Balances and simplified Prospects for any geographical area of Ecuador. In addition, methodologies are applied to a practical case related to the concession area of the Southern Regional Electricity Company (EERSSA) for the study horizon 2020-2040. With regard to the methodological proposal for the elaboration of Energy Balances, it is proposed the development of the methodology in five faces denominated: Energy chains, active chains, data management, energy balances and energy statistics. As for the methodology to realize simplified Energy Prospectives, its development is proposed in 3 phases: Study and demand management, Simulation and analysis of the energy matrix and Energy statistics.